(untitled) (El-Wahat Journal for Research and Studies, 2026)
Algeria’s endeavour to set in motion comprehensive economic development hinges upon the scale and quality of investment, which ought to be framed and regulated by legal instruments that entrench principles, guarantees and financial incentives. These instruments must safeguard investors’ rights and projects and cultivate confidence and reassurance in the Algerian investment climate. Against this backdrop, the Algerian legislature, in Law No. 22-18 on the Promotion of Investment, articulated the general principles underpinning investment in Algeria. What distinguishes these principles is their entrenchment in the 2020 constitutional amendment, signaling their legal weight and elevated, stable status. The Law guarantees the freedom of investment, equality among investors, and the transparency necessary for the realisation of projects, while reassuring investors through the guarantee of legislative stability in accordance with the principle of legal certainty.